2001
DOI: 10.1155/2001/954340
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cell Myocarditis in a Patient With Crohn's Disease, Treated with Etanercept – A Tumour Necrosis Factor-Alpha Antagonist

Abstract: Cardiac disease in association with inflammatory bowel disease (IBD) is uncommon. Reports include pericarditis, pericardial effusion, myocarditis, myocardial infarction, endocarditis and arrythmias. Myocardial inflammation related to IBD may be due to a drug hypersensitivity reaction or micronutrient deficiency, or may be secondary to the underlying IBD as an extraintestinal manifestation. In this setting, myocarditis usually presents as congestive heart failure and/or refractory arrhythmia. Prognosis varies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Although patients with a hypersensitivity disease may develop arteritis, acute myocardial infarction rarely occurs (5). In several studies, development of giant cell myocarditis was shown hystologically in the course of otoimmune disorders such as Crohn's disease (6). Mesalazine associated eosinophilic myocarditis or giant cell myocarditis was considered in our case.…”
Section: öZetmentioning
confidence: 72%
“…Although patients with a hypersensitivity disease may develop arteritis, acute myocardial infarction rarely occurs (5). In several studies, development of giant cell myocarditis was shown hystologically in the course of otoimmune disorders such as Crohn's disease (6). Mesalazine associated eosinophilic myocarditis or giant cell myocarditis was considered in our case.…”
Section: öZetmentioning
confidence: 72%
“…Myocarditis (cardiac muscle inflammation) is associated with symptoms of congestive cardiac failure, chest pain, arrhythmias, syncope, and sudden death [13]. Myocarditis can be broadly classified into infective and noninfective causes.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory bowel disease is uncommonly associated with cardiac disease [13]. These extraintestinal manifestations include pericarditis, pericardial effusion, myocarditis, myocardial infarction, endocarditis, and arrhythmias [1, 3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently a 46-year-old male patient who had moderately active Crohn's colitis presented with congestive heart failure from biopsy-proven giant cell myocarditis [27]. The patient's bowel disease was resistant to corticosteroids, and his myocarditis developed while he was on prednisone, 15 mg/d.…”
Section: Myocarditismentioning
confidence: 99%